npj Mental Health Research - Tsai, Jack.; Vinogradov, Sophia; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Mental Health Research considers all aspects of research that aims to understand, diagnose, and treat mental health disorders, while also enhancing overall well-being, building resilience, and promoting optimal functioning at both individual and population levels. The journal covers a broad range of topics including but not limited to: Public and community mental health Mental health services research Mental health policy Social determinants of mental health Psychopharmacoepidemiology Pathophysiology of neuropsychiatric disorders Basic, preclinical, and clinical research into the diagnosis and treatment of neuropsychiatric disorders New methodologies and technology-based interventions The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by mental health experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Mental health; Mental illness; Psychiatry; Psychology; Mental Health; Mental Disorder; Psychiatry; Behavioral Sciences and Psychology